Emotions and psychological mechanisms of listening to music in cochlear implant recipients - YÜKSEL, MUSTAFA; SARLIK, ESRA; ÇİPRUT, AYŞE AYÇA (My University, 2023)
OBJECTIVES: Music is a multidimensional phenomenon and is classified by its arousal properties, emotional quality, and structural characteristics. Although structural features of music (i.e., pitch, timbre, and tempo) and music emotion recognition in cochlear implant (CI) recipients are popular research topics, music-evoked emotions, and related psychological mechanisms that reflect both the individual and social context of music are largely ignored. Understanding the music-evoked emotions (the \"what\") and related mechanisms (the \"why\") can help professionals and CI recipients better comprehend the impact of music on CI recipients\" daily lives. Therefore, the purpose of this study is to evaluate these aspects in CI recipients and compare their findings to those of normal hearing (NH) controls. DESIGN: This study included 50 CI recipients with diverse auditory experiences who were prelingually deafened (deafened at or before 6 years of age)-early implanted (N = 21), prelingually deafened-late implanted (implanted at or after 12 years of age-N = 13), and postlingually deafened (N = 16) as well as 50 age-matched NH controls. All participants completed the same survey, which included 28 emotions and 10 mechanisms (Brainstem reflex, Rhythmic entrainment, Evaluative Conditioning, Contagion, Visual imagery, Episodic memory, Musical expectancy, Aesthetic judgment, Cognitive appraisal, and Lyrics). Data were presented in detail for CI groups and compared between CI groups and between CI and NH groups. RESULTS: The principal component analysis showed five emotion factors that are explained by 63.4% of the total variance, including anxiety and anger, happiness and pride, sadness and pain, sympathy and tenderness, and serenity and satisfaction in the CI group. Positive emotions such as happiness, tranquility, love, joy, and trust ranked as most often experienced in all groups, whereas negative and complex emotions such as guilt, fear, anger, and anxiety ranked lowest. The CI group ranked lyrics and rhythmic entrainment highest in the emotion mechanism, and there was a statistically significant group difference in the episodic memory mechanism, in which the prelingually deafened, early implanted group scored the lowest. CONCLUSION: Our findings indicate that music can evoke similar emotions in CI recipients with diverse auditory experiences as it does in NH individuals. However, prelingually deafened and early implanted individuals lack autobiographical memories associated with music, which affects the feelings evoked by music. In addition, the preference for rhythmic entrainment and lyrics as mechanisms of music-elicited emotions suggests that rehabilitation programs should pay particular attention to these cues.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KULAK BURUN BOĞAZ; Clinical Medicine (MED); CLINICAL MEDICINE; OTORHINOLARYNGOLOGY; Konuşma ve İşitme; Otorhinolaryngology; Speech and Hearing